Rethinking the limits of climate change adaptation - Ma. Laurice Jamero; Miguel Esteban; Christopher Chadwick; Motoharu Onuki (Asian Development Bank (ADB), 2019)
Using a case study approach, this research explores the various potential limiting factors of climate change adaptation, based on the experience of four low-lying islands in central Philippines. In the aftermath of the 2013 7.2-magnitude Bohol earthquake, the islands now become flooded even during normal spring tides. Results show that, while development problems can constrain adaptive capacity against climate hazards, the outlook of the affected communities about their future on their home islands may ultimately determine the limits of adaptation. As social factors may play a greater role in adaptation than environmental factors, climate-smart development is needed, as well as proper education regarding climate risks and available adaptation options.
Keywords: Q00; 330; agriculture; sampling methods